Db2 skeleton cloning : protecting your production environment - Bartak, Paul; Willging, Tim (IBM redpaper., 2017)
IBM Db2® for z/OS® is well known as the gold-standard information steward. Deep synergy with the z/OS operating system and System Z platform provides support for the highest transaction volumes with the ultimate levels of availability. Just like any high-performance engine, occasional maintenance or upgrades are needed to maintain peak performance and to incorporate new features. Those that demand the highest standards and protection of their production environments know that you want to test changes outside of production first. It is common to have development or test environments for application development and verification. What about applying Db2 maintenance or performing migrations to new version or release levels? Sure, you probably perform these activities outside of production first, but are these environments similar enough to production to surface the same results as those you might encounter in production? Your production Db2 Catalog & Directory often has a different mix and complexity of objects, which were created at different levels of Db2, that can span decades of time. The best test of these activities is against your production system, but this is the system that we want to protect. How can we accomplish this? Clone it! Skeleton cloning produces a specific kind of clone, which provides a replica of the portions of your Db2 production environment that are needed to complete your testing. You can use the skeleton clone to find issues before they occur in production. This process allows you to refine maintenance steps in a safe environment and to minimize potential downtime when performing the same steps in a production system. This IBM® Redpaper"!publication gives a high-level overview of the IBM Db2 Cloning Tool and includes specific use cases for the tool. It also details the skeleton cloning process, which you can use to test migration, function levels, and maintenance, and includes demo examples that show a Db2 11 to 12 migration test using skeleton cloning